Shabbat-at-Camp at Three Jewish Camps: Jewish Learning Through Ritual Participation. Issue 4 (2nd October 2018) - Reimer, Joseph
ABSTRACT: Given the centrality of Shabbat celebration to the weekly cycle of Jewish residential camps, it is surprising how little Shabbat-at-camp has been studied. This participant observational study of three American Jewish residential camps has focused on how Shabbat-at-camp is created and how the ritual celebrations engage the older campers. This study found that when these camps encourage ritual innovation and invite their oldest campers to take leadership in ritual practice, the teens respond with great energy and dedication. Drawing a detailed portrait of these invented rituals, I argue that behind the carnival atmosphere lies a serious invitation to four distinct Jewish learning opportunities and a path to becoming leaders in their camp world.